Analisis Estimasi Produksi Kelapa di Kabupaten Padang Pariaman - M Afdal S; Hasdi Aimon; Alpon Satrianto (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2019)
This research purpose are to estimate and explained the impact of number of coconut plants and labor to production of coconut in Padang Pariaman regency. The type of this research is descriptive research, the data used are primary and secondary data and analyzed using Multiple Linear Regression. The estimation results show that the number of coconut plants has a positive and significant effect on the amount of coconut production in Padang Pariaman Regency and the labor has a not significant positive effect on the amount of coconut production in Padang Pariaman Regency.